WORK PLACE BASED ASSESSMENT IN FOUNDATION YEAR: FOUNDATION UNIVERSITY MEDICAL COLLEGE EXPERIENCE - Rauf, Shahid; Aurangzeb, Wajeeha; Abbas, Seyyedha; Sadiq, Naushaba (Journal of Ayub Medical College Abbottabad, 2011)
Background: In year 2011 the Department of Medical Education, Foundation University Medical College, Rawalpindi decided to implement workplace based assessments (WPBA) in the upcoming batch of students. The formative assessment included Mini-Cex, Direct Observation of Procedural Skills (DOPS), case-based discussions (CbD) and multisource feedback (MSF). The study was undertaken to explore and determine the perceptions of the surgical trainees and faculty regarding their experiences in WPBA. Methods: In this descriptive cross-sectional study, a 24 item, 5 point Likert scale questionnaire was administered to 30 trainees and 20 faculty members of surgery department at Foundation University Medical College. The questionnaire had reasonably high reliability (Î±=0.90). The results were analysed and tabulated using SPSS-16. The perceptions of faculty and trainee on WPBA were analysed separately for assessing the effectiveness of the assessment method. Results: Majority of the respondents were of the view that WPBA is beneficial and should be continued. However the trainees were of the view that it should be free of the personal preferences of the trainer. Moreover the training workshops for faculty and trainee should be regular and frequent. Conclusions: WPBA offers the opportunity to connect teaching, learning and assessment. More studies on WPBA in different departments of hospitals are required to be carried out in order to overcome the deficiencies and to improve the assessment methods. Keywords: WPBA, FUMC, Mini-Cex, DOPS, CBD